CONNOR-DAVIDSON RESILIENCE SCALE (CD-RISC-25) ADAPTATION IN LATVIAN SAMPLE - Skaldere-Darmudasa, Gunita; Sudraba, Velga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The aim of the research was to adapt the full version of Connor-Davidson Resilience scale (CD-RISC-25) in Latvia to gain qualitative and valid psychological measure of assessing resilience. Studying the scientific literature has shown multidimensional nature of resilience construct as well as broaden the knowledge about resilience as complicated psychological construct which can be affected by different factors rising from one’s individual experience and the environment where he comes from. Sample (N=186) in age range 18 to 69 years old (M=37.65; SD=12.07), 75.8% females. Participants filled demographic data questionnaires and Connor-Davidson Resilience Scale (Connor & Davidson, 2003). Scale of 25 items, each rated in 5-point Likert’s scale (0-4), with higher scores reflecting greater resilience. Cronbach’s Alpha for all items varies from .88 to .90 and for scale total α= .89, which proves good internal consistency. Test-retest reliability demonstrated a high level of agreement, with an intraclass correlation coefficient of .93. The Connor-Davidson Resiliency Scale in Latvian sample showed high internal consistency α = .89 and good psychometric properties, same as noted in other studies (Connor & Davidson, 2003). This proves CD-RISC-25 as qualitative and a valid measure for further studies of resilience in Latvian population.